2014
DOI: 10.1111/bjet.12149
|View full text |Cite
|
Sign up to set email alerts
|

The rhetoric of reform and teachers' use of ICT

Abstract: During the last two decades, the Cyprus Education System has been undergoing systematic reform efforts. Within the spirit of change, efforts have been made to equip all public schools with computers and provide them with access to the internet. Compared with other European Union countries, Cyprus infrastructure is one of the most developed. However, as our research shows, the adoption of technology does not match the rhetoric of reform that dominates education discourse. In order to examine the challenges and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 13 publications
2
52
0
Order By: Relevance
“…The first factor was the school climate and trust within the school, and the second factor was the existence of networks for accessing new information. Other recent research in Cyprus indicates that, although teachers believe that using ICT can transform education and are willing to use it, little real change is occurring in schools (Vrasidas 2014). The major barriers appear to be lack of time, lack of flexibility in curriculum, and lack of access to ICT and support.…”
Section: 2mentioning
confidence: 98%
“…The first factor was the school climate and trust within the school, and the second factor was the existence of networks for accessing new information. Other recent research in Cyprus indicates that, although teachers believe that using ICT can transform education and are willing to use it, little real change is occurring in schools (Vrasidas 2014). The major barriers appear to be lack of time, lack of flexibility in curriculum, and lack of access to ICT and support.…”
Section: 2mentioning
confidence: 98%
“…Related to these results, Albion et al (2015) report that one way of changing classrooms practices is to work with the teachers' beliefs about ICT for teaching and learning. According to Vrasidas (2015), national governmental directives that require teachers to use ICT is challenging. Vrasidas writes that:…”
Section: Reason 2: the Challenged Teachermentioning
confidence: 99%
“…Tsai and Chai (2012) have argued that teachers' design capacities are third-order barriers that hinder ICT integration besides the first-order barriers (e.g., access to technology) and second-order barriers (i.e., teachers' beliefs). Studies from many developed countries have shown that despite good access to technology and teachers' support in ICT use, teachers' integration of ICT is still limited, especially for constructivist-oriented use (e.g., Vrasidas, 2015). This phenomenon is not surprising, as contextually, teachers are required to design specific lessons for the group of students who have particular learning trajectories and relationships with the teacher.…”
Section: Tpack For 21st Century Learningmentioning
confidence: 99%